LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRMA TERHADAP PERILAKU MEROKOK SISWA MADRASAH ALIYAH KELAS X - Muhammad Royani; Siti Fatimah; Reza Pahlevi (IKIP Siliwangi, 2022)
This study aims to examine the implementation of group guidance services using sociodrama techniques on the smoking behavior of students of Madrasah Aliyah class X at the integrated MA Alhuda Cililin, to find out how students respond in service activities, as well as to observe what difficulties students feel during service activities, and observe obstacles faced by BK teachers in the process of service delivery. This study uses descriptive qualitative methods with data collection techniques using observation, interviews and documentation studies, and processed using triangulation. The data in this study is the result of interviews with the BK teacher and three samples of students from class X. This service consists of the initial stage, the core stage and the final stage. Service activities are carried out as many as one meeting which is carried out in the classroom. Implementation of service activities runs effectively, where students show the development of a good understanding of the dangers of smoking behavior. The student's response was quite good, seen from the activeness of students when attending and watching the sociodrama that was displayed. The difficulties felt by students in the process of implementing the service existed in a fairly short time and most students did not want to be a group of sociodrama players. The obstacles faced by BK teachers are time, infrastructure and some students who are still shy and awkward so they must be given direction. Keywords:Group Guidance, Sociodrama Techniques, Smoking Behavior.Keywords: